2020
DOI: 10.1371/journal.pone.0235504
|View full text |Cite
|
Sign up to set email alerts
|

The sound sensation of a pure tone in cochlear implant recipients with single-sided deafness

Abstract: Ten cochlear implant (CI) users with single-sided deafness were asked to vary the parameters of an acoustic sound played to their contralateral ear to characterize the perception evoked by a pure tone played through the direct audio input of their CI. Two frequencies, centered on an apical and a medial electrode, were tested. In six subjects, the electrode positions were estimated on CT scans. The study was divided in 3 experiments in which the parameters of the acoustic sound varied. The listeners had to vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The literature is mixed regarding the question of CI pitch plasticity. Some studies have shown pitch perception to shift toward the sound-processor frequency allocation (Reiss et al, 2014;Hu and Dietz, 2015;Tan et al, 2017), and others have not (Schatzer et al, 2014;Aronoff et al, 2016;Marozeau et al, 2020). One possible reason for the disparate results is that the procedures (Jensen et al, 2021) and stimuli (Adel et al, 2019) used have a large impact on the observed results, questioning whether these measurements reflect place of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The literature is mixed regarding the question of CI pitch plasticity. Some studies have shown pitch perception to shift toward the sound-processor frequency allocation (Reiss et al, 2014;Hu and Dietz, 2015;Tan et al, 2017), and others have not (Schatzer et al, 2014;Aronoff et al, 2016;Marozeau et al, 2020). One possible reason for the disparate results is that the procedures (Jensen et al, 2021) and stimuli (Adel et al, 2019) used have a large impact on the observed results, questioning whether these measurements reflect place of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown plasticity toward clinical CFs (Reiss et al, 2014;Hu and Dietz, 2015;Tan et al, 2017) while others have shown little such evidence. For example, Aronoff et al (2016) found that BI-CI pitch matches often deviate from numbermatched electrodes, while Schatzer et al (2014) and Marozeau et al (2020) found that SSD-CI pitch matches align more closely with radiographic estimates of electrode position than with clinical CFs.…”
Section: Discussionmentioning
confidence: 99%
“…A speech vocoder is a valuable tool for studying speech perception in CI listeners as it simulates speech performance of CI listeners with NH listeners. Although there is a common misconception that listening through a vocoder is equivalent to listening through a CI, several studies have shown that this is not the case ( Karoui et al, 2019 ; Marozeau et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%